Student perceptions toward virtual reality training in dental implant education - Yue Huang; Yingwen Hu; Unman Chan; Pengyu Lai; Yueting Sun; Jun Dai; Xin Cheng; Xuesong Yang (PeerJ, 2023)
Objectives Both the shortage of professional teaching resources and the expensive dental implant supplies impede the effective training of dental undergraduate in implantology. Virtual reality (VR) technology may provide solutions to solve these problems. This pilot study was implemented to explore the usability and acceptance of a VR application in the training of dental implant among dental students at the Jinan University School of Stomatology. Methods We designed and developed a VR system with head-mounted displays (HMDs) to assist dental implant training. Undergraduate dental students were invited to experience a 30-minute “Introduction to dental implants” VR-HMDs training module. A total of 119 dental students participated the training. Firstly, the VR interactive training on dental implant was described, illustrated and practiced. Next, a system usability scale (SUS) survey was used to verify the usability and feasibility of the VR application on training dental students. Finally, the participants were given a questionnaire to provide their perceptions and feedback of the usefulness of the VR application for training dental implant skills. Results The SUS score was 82.00 ± 10.79, indicating a top 10 percentage ranking of the system’s usabilitys. The participants’ answers to the questionnaire reflected most of them exhibited strong interests in the VR system, with a tendency that the female students were more confident than the male in manipulating the VR system. The participants generally acknowledged the usefulness of VR dental implants, ranking VR value above the traditional laboratory operations, and a preference for using the VR system on learning other skills. They also gave valuable suggestions on VR dental implants for substantial improvement. However, some students were not strongly positive about the VR training in this study, the reason might lie in a more theoretical module was selected for testing, which impacted the students’ ratings. Conclusions In this study we revealed the feasibility and usability of VR applications on training dental implant among undergraduate dental students. This pilot study showed that the participants benefited from the dental implant VR training by practicing the skills repeatedly. The feedback from student participants affirmed the advantages and their acceptance of the VR application in dental education. Especially, the VR-based technology is highly conducive to clinical operating skills and surgical procedures-focused training in medical education, indicating that the VR system should be combined with the traditional practice approach in improving dental students’ practical abilities.